The Russian Revolutions Of 1917 : The Northern Impact and Beyond. - Myklebost, Kari Aga. (Academic Studies Press, 2020)
The Russian Revolutions of 1917: TheNorthern Impact and Beyond consists of twelve articles, written by leadingscholars from Russia, Norway, Sweden and Great Britain. They deal with therepercussions of these revolutions in Russia and Scandinavia, especially in theNorthern parts of these countries.